ICT Material Teachers’ Attitudes Towards Addition It for Grades Five And Six (A Field Study on A Sample of Teachers in The First Cycle of Basic Education in Lattakia) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aimed to investigate the ICT teachers’ attitudes towards the addition ICT material for grades five and sixو and the effect of  job situation, sex and years of teaching experience of these attitudes. To achieve the research objectives the descriptive method was used, and the questionnaire was administered and distributed to a random sample of (60) teachers. The study arrived at the following results: 1.The attitude of ICT teachers in the city of Lattakia towards the addition ICT material for grades five and six was positive. 2.There are significant differences at (a = 0, 05) between the average grade of ICT teachers in their attitudes towards the addition ICT material for grades five and six according to the job Situation variable, The results were favor of specialized in the field of informatics in their studies. 3.There are significant differences at (a = 0, 05) between the average grade of ICT teachers of the sample in their attitudes towards the addition ICT material for grades five and six according to the gender variable, The results were favor of male. 4.There are no significant differences at (a = 0, 05) between the average grade of ICT teachers in their attitudes towards the addition ICT material for grades five and six according to the years of teaching experience variable. Finally, the study ended with some conclusions and recommendations as Include the share of  ICT within the study plan and organizing training courses to improve the ability of teachers to teach ICT for pupils in the fifth and sixth grades. يهدف البحث إلى تعرّف اتجاهات معلمي مادة تكنولوجيا المعلومات والاتصالات نحو إدخال هذه المادة في الصّفين الخامس والسّادس، وعلاقتها بمتغيرات الوضع الوظيفي، والجنس، وعدد سنوات الخبرة. ولتحقيق أهداف البحث تمَّ استخدام المنهج الوصفي، وأُعدت استبانة الاتجاهات ووزعت على عينة عشوائية بسيطة مكونة من (60) معلماً ومعلمة، ثم جُمعت البيانات وحُللت إحصائياً، وتوصل البحث إلى النّتائج الآتية: • كانت اتجاهات معلمي مادة تكنولوجيا المعلومات والاتصالات في مدينة اللاذقية نحو إدراج المادة ضمن مناهج الصّفين الخامس والسّادس إيجابية بشكل عام.• وجود فرق دال إحصائياً بين المتخصصين بمجال المعلوماتية في دراستهم والذين خضعوا لدورة تأهيل معلمي المعلوماتية في اتجاهاتهم نحو إدخال المادة في الصفين الخامس والسّادس، لصالح المتخصصين بمجال المعلوماتية في دراستهم.• وجود فرق دال إحصائياً بين الذّكور والإناث من أفراد العينة في اتجاهاتهم نحو إدخال المادة في الصّفين الخامس والسّادس، لصالح الذّكور.• عدم وجود فرق دال إحصائياً بين المعلمين في اتجاهاتهم نحو إدخال المادة في الصفين الخامس والسّادس، تبعاً لمتغير عدد سنوات الخبرة بتعليم المادة. وانتهى البحث بمجموعة من الاستنتاجات والتّوصيات كإدراج حصة المعلوماتية داخل الخطة الدّرسية، وتنظيم الدّورات التّدريبية لتحسين قدرة المعلمين على تعليم المعلوماتية لتلاميذ الصّفين الخامس والسّادس.